Assessing Validity of the Target Parameters of the «Energy Strategy of Ukraine till 2035» Based on Materiality Guideline - Perfilova Oleksandra Ye. (Problemi Ekonomiki, 2015)
The article describes the results of assessing the provisions of the project «Energy Strategy of Ukraine till 2035» in terms of the validity of the main target parameters of the strategy. The assessment is based on critical rethinking of the essence of choosing certain indicators as strategic target parameters. This gave the opportunity to prove the existing rigidity of approaches to developing energy policies in Ukraine, which is confirmed by studying the national energy policy foundations in accordance with the chronology of the emergence of the state energy strategies. In order to check the validity of the provisions of the project «Energy Strategy of Ukraine till 2035» it has been proposed to use materiality guideline, as it enables to set a limit of allowable information distortion, exceedance of which becomes critical from the point of impact on the process of making strategic decisions. It has been found that the forecast balances of consuming the fuel and energy resources till 2035 were made up without taking into account the essential information about the energy intensity of GDP and its structure, which gives grounds to draw a conclusion on invalidity of some target parameters of the project.